Blinded by the light? Analyzing sustainability authenticity, customer service perceptions, and halo effects. Issue 1 (11th February 2019) - Amos, Clinton; Brockhaus, Sebastian; Fawcett, Amydee M.; Fawcett, Stanley E.; Knemeyer, A. Michael
Abstract : Purpose: The purpose of this paper is to evaluate how service perceptions influence customer views of the authenticity of corporate sustainability claims. The goal of this paper is to help supply chain decision-makers better understand boundary conditions in order to design more enduring and impactful sustainability programs. Design/methodology/approach: The authors employ behavioral experiments, subjecting two theoretically derived hypotheses to verification across five diverse industries and two distinct sustainability vignettes. Findings: Customer service perceptions emerge as a significant boundary condition to the perceived authenticity of sustainability efforts. Subjects attributed significantly higher authenticity toward sustainability efforts in above average vs below average service quality contexts. Further, respondents attributed deceptive motivations to sustainability efforts at companies with below average service. Research limitations/implications: The authors confirm the underlying tenet of social judgment theory, which suggests that a priori perceptions create a zone of acceptability or rejection. Ultimately, investing in sustainability can lead to counterproductive cynicism. Practical implications: The authors infer that customers' willingness to give companies credit for sustainability initiatives extends beyond service issues to any practice that influences a priori perceptions. Supply chain managers must rethink their role in designing both customer service and sustainability systems to achieve positive returns from sustainability investments. Originality/value: The authors challenge the assumption that customers universally positively view sustainability efforts. If customers hold a priori negative service perceptions, otherwise well-designed sustainability programs may invoke cynical reactions. Thus, sustainability programs may not inoculate firm reputations from adverse incidents. Given they touch both service and sustainability systems, supply chain managers are positioned to holistically influence their design for competitive advantage.